Study of TP53 Gene-Codon 72 Polymorphism in Epithelial Ovarian Cancer (EOC) - Khalid A. Hadi; Ali R Mulakhudair (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: The tumor-suppressor gene (TP53) encodes p53 protein, the vital protein in the apoptoticcascade pathway which has been presented to be of crucial potential in the progression of cancers. Geneticvariation SNP that were revealed to affect the regulatory biochemical functions of p53 are the exon 4 codon72, (G)Arg/(C)pro polymorphisms. Aim: the present study aims to analyses genetic variation (SNP) of Tp53gene, codon 72 and p53 protein level in Epithelial Ovarian Cancer (EOC). Methods: the study achieved on 26EOC cell line specimens and 26 specimens as control group, using PCR-RFLP genetic analysis method andcell lysate p53 level determined by ELISA technique. Results: the percentage of allele polymorphism comeas homologous GG variant 85% and 23% in EOC specimens and control respectively and (CC) (8% and46%) in EOC case and the control in order. Heterologous pattern CG was (34% and 23%) for experimentaland control group respectively.Conclusion: our study proposes that 72 codon polymorphism (GG) is closely related to EOC progressions.